Penggunaan Media Photography Essay Di MAN 1 Kota Gorontalo - Hendra Hendra; Ahmad Syamsu Rijal (Universitas Negeri Gorontalo, 2022)
The success of the learning process is the responsibility of all parties in the world of education. All roles must be executed properly. The achievement of learning objectives is an indicator of the achievement of all processes carried out during learning. The function of the learning media essentially has a significant impact on learning. Because the learning media will give an impression in the process of interaction between teachers and students and the learning environment. the use of a photography essay will provide a more concrete explanation of the object through a photo, and of course it can be well received. The method used in this service is participatory dissemination. Involve participants directly in the form of mentoring. The service was carried out well, the results of the pres test showed 9 students, 4 people in the sufficient category and 3 people in the good category. And the post test showed a very significant change, namely 16 people in the good category.